Investigating the Use of Computer for Language Teaching among Pakistani EFL Teachers - Abdul Aziz, Asma; Muhammad Pervaiz; Ul Hassan, Mehmood (Pakistan Languages and Humanities Review, 2022)
The present study investigated the current situation of EFL teachers in Balochistan, Pakistan by exploring issues and challenges faced by them in using Computer-Assisted Language Instruction. The study was quantitatively based on a descriptive survey design. The questionnaire was constructed using a five-point Likert scale and data were collected from 150 English language teachers currently teaching at higher secondary schools in Pakistan at District Sibi Balochistan, Pakistan. The findings of the study revealed that EFL teachers face various issues and challenges like non-availability of computers and laptops, shortage of electricity, lack computer education, theoretically-based course work, lack of interest from senior teachers towards learning or using computers, and insufficient time for Computer-Assisted Language Instruction. Besides, many female English language teachers are unable to operate computers. They have to do domestic duties and cannot afford extra time for learning computers. The study concludes that, without addressing these issues, inculcating the use of Computer-Assisted Language Instruction is a complex phenomenon in Pakistan. Hence, policy makers, stakeholders and administrative staff should target these issues so that the advantages of Computer-Assisted Language Instruction in teaching may be provided to teachers in higher secondary schools in Pakistan.